Fundamental determinants of school efficiency and equity: German states as a microcosm for OECD countries - Ludger Wößmann (Institute for the Study of Labor (IZA), 2007)
Cross-country evidence on student achievement might be hampered by omitted country characteristics such as language or legal differences. This paper uses cross-state variation in Germany, whose sixteen states share the same language and legal system, but pursue different education policies. The same results found previously across countries hold within Germany: Higher mean student performance is associated with central exams, private school operation, and socio-economic background, but not with spending, while higher equality of opportunity is associated with reduced tracking. In a model that pools German states with OECD countries, these fundamental determinants do not differ significantly between the two samples.
Keywords: 330; Bildungsniveau; Bildungspolitik; Bildungschancen; Wirtschaftliche Effizienz; Teilstaat; Deutschland; Vergleich; OECD-Staaten